Investment Multiplier Effect of Hajj Funds on Economic Growth in Indonesia - Riyan Andni; Syukri Fathudin Achmad Widodo; Arief Hidayat Afendi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This study aims to measure the multiplier effect coefficient of investment in Hajj funds held by the Hajj Financial Management Agency (BPKH) starting in 2017-2021 on the country’s economy. Data was collected from BPKH and Central Statistics Agency (BPS) publications. This type of research is a descriptive quantitative analysis of the economic balance equation, namely Y= C I+G, with the multiplier effect coefficient analysis tool. The results showed that BPKH Investment had a positive effect on economic growth. Still, the Multiplier Value of Hajj fund investment by BPKH showed that the allocation had not demonstrated awareness of the multiplier number in channelling investment instruments. BPKH focused on studying investment instruments that provide returns in increasing the funds of prospective pilgrims so that the results are significant in driving economic growth. Reviewing the mechanisms in channelling investments, such as embracing MSMEs as financing recipients and allocating investment budgets for labour-intensive projects, is necessary.